100 questions & answers about peripheral artery disease (PAD) - Mohler, Emile R.; Hirsch, Alan T. (Alan Tick) (Sudbury, Mass. : Jones and Bartlett Publishers, 2010)
"What is Pad? What are the symptoms of PAD? Is there a cure for PAD? When might I need an angioplasty? How do I gain control over my life now that I have PAD?" -- Cover, p.1
Peripheral artery disease (PAD) epidemiology and prevalence -- PAD pathophysiology -- Symptoms and physical findings of PAD -- PAD diagnosis -- PAD risk factors -- Heart attack, stroke, and limb loss in individuals with PAD -- Lowering risk : treatment of atherosclerosis risk factors and use of antithrombotic (anticlotting) medications -- Noninvasive treatment of claudication -- Invasive treatment of claudication -- Your doctor's visit -- Further information on PAD
Includes index
13
Keywords: Arterial Occlusive Diseases -- Popular Works; Peripheral vascular diseases -- Miscellanea; Peripheral Vascular Diseases -- Popular Works